Clinical importance of lactic acid bacteria: a short review - Kumari, A.; Catanzaro, R.; Marotta, F. (Acta Biomedica Atenei Parmensis, 2012)
Abstract. Lactic acid bacteria (LAB) were used extensively as starter cultures in food fermentation. Some of the health benefits which have been claimed for lactic acid bacteria as probiotics include the following: improvement of the normal microflora, prevention of infectious diseases and food allergies, reduction of serum cholesterol, anticarcinogenic activity, stabilization of the gut mucosal barrier, immune adjuvant properties, alleviation of intestinal bowel disease symptoms and improvement in the digestion of lactose in intolerant hosts. The present study is aimed to brief review the some clinical importance of lactic acid bacteria.